If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7r + 2 = 5(r + -4) Reorder the terms: 2 + 7r = 5(r + -4) Reorder the terms: 2 + 7r = 5(-4 + r) 2 + 7r = (-4 * 5 + r * 5) 2 + 7r = (-20 + 5r) Solving 2 + 7r = -20 + 5r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-5r' to each side of the equation. 2 + 7r + -5r = -20 + 5r + -5r Combine like terms: 7r + -5r = 2r 2 + 2r = -20 + 5r + -5r Combine like terms: 5r + -5r = 0 2 + 2r = -20 + 0 2 + 2r = -20 Add '-2' to each side of the equation. 2 + -2 + 2r = -20 + -2 Combine like terms: 2 + -2 = 0 0 + 2r = -20 + -2 2r = -20 + -2 Combine like terms: -20 + -2 = -22 2r = -22 Divide each side by '2'. r = -11 Simplifying r = -11
| 7p+2=5p+8 | | 3(5x-1)=9 | | 10x+3-6x=-21 | | -3m+6-5(m-1)=-5m-(2m-4)+5 | | -11(x+3)+18=(8-3x)7 | | 2(w-(2w+4)+3)=2(w+1) | | 6(7x+18)=(x+8)4 | | 4(3x+6)=5(x-5) | | 7(x-11)=12x-122 | | 2x+3(x-4)=2(x-3) | | 28-32x=92 | | 19x-32=63 | | 9x+19=-35 | | -12x=28-16x | | 17x-35=271 | | 9x+13=-68 | | -15x-28=-73 | | -5x+8=48 | | 2(x+3)=-4(x+1) | | 73-x=18 | | 7x+32=4 | | -4x+5=-15 | | -5x-8=12 | | 3(2t-4)=20-2t | | 10x+7=27 | | 45-13x=58 | | 16x-55=41 | | (10x+5)+(6x+1)=180 | | 7x+15=-20 | | 13x-29=153 | | 6x+14=-64 | | 7x-5x+15=x+8 |